Trehalose-based neuroprotective autophagy inducers. (15th May 2021) - Assoni, Giulia; Frapporti, Giulia; Colombo, Eleonora; Gornati, Davide; Perez-Carrion, Maria Dolores; Polito, Laura; Seneci, Pierfausto; Piccoli, Giovanni; Arosio, Daniela
Graphical abstract: Abstract: A small set of trehalose-centered putative autophagy inducers was rationally designed and synthesized, with the aim to identify more potent and bioavailable autophagy inducers than free trehalose, and to acquire information about their molecular mechanism of action. Several robust, high yield routes to key trehalose intermediates and small molecule prodrugs (2 –5 ), putative probes (6 –10 ) and inorganic nanovectors (12a – thiol-PEG-triazole-trehalose constructs 11 ) were successfully executed, and compounds were tested for their autophagy-inducing properties. While small molecules 2 –11 showed no pro-autophagic behavior at sub-millimolar concentrations, trehalose-bearing PEG-AuNPs 12a caused measurable autophagy induction at an estimated 40 μM trehalose concentration without any significant toxicity at the same concentration.